Development of EDUDA as a Media to Build Students 'Self-Resistance in Preventing Drugs - Martiano Martiano (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
The use of drugs, especially in Sumatera Utara, Indonesia, has a fairly large increase and requires serious efforts. EDUDA is an application that can help students form their resilience assisted by counseling guidance teachers, parents, and peers in forming good character. The educational application has self-defense materials and direct assessment of students' self-resistance which can be seen by the counseling teacher as an evaluation material for improving the quality of student development. based on the results of the implementation of educational media in schools, namely in phase 1 the increase was 7.3 with an average of 84.55, in phase 2 the increase was 3.24 with an average of 87.73. whereas in phase 3 the increase was 3.27 with an average of 91.06. the increase in phase 3 has been proven in building students' self-resistance in preventing drugs